IOS programming : the Big Nerd Ranch guide - Conway, Joe (Big Nerd Ranch ; Pearson Technology Group (distributor), 2012)
Presents a guide to the concepts and coding of iOS to create a variety of applications, covering such topics as debugger, core location, reference counting, blocks and categories in Objective-C, and push notifications.